Genotyping and molecular characteristics of multidrug-resistant Mycobacterium tuberculosis isolates from China. Issue 4 (April 2015) - Zhang, Zhijian; Lu, Jie; Liu, Min; Wang, Yufeng; Qu, Geping; Li, Hongxia; Wang, Jichun; Pang, Yu; Liu, Changting; Zhao, Yanlin
Summary: Objectives: The aim of this study was to explore the population structure of multidrug-resistant (MDR) tuberculosis strains and distribution of resistance-associated nucleotide alteration among the different genotype MDR strains in China. Methods: The genotypes of 376 MDR strain were analyzed by 15-loci MIRU-VNTR and RD105 deletion-targeted multiplex PCR (DTM-PCR) method. In addition, all the MDR isolates were sequenced for genetic mutations conferring rifampicin ( rpoB ) and isonizid resistance ( katG, inhA and oxyR - ahpC ). Results: Among the 376 MDR isolates, 261 (69.4%) belonged to Beijing genotype, including 177 modern Beijing strains (67.8%) and 84 ancient Beijing (32.2%) strains. The percentages of streptomycin-resistant, kanamycin-resistant, pre-XDR and XDR TB in modern Beijing genotype were significantly lower than ancient genotype ( P < 0.05). The Beijing MDR strains had significantly higher proportions of ofloxacin-resistant and pre-XDR isolates than non-Beijing strains ( P < 0.01). In addition, the clustering rate of modern Beijing strains was significantly higher than that of ancient Beijing strains (46.3% vs. 11.9%, P < 0.01). 94.7% and 79.3% of MDR isolates harbored genetic mutations conferring rifampicin and isonizid resistance, respectively, and the most prevalent mutation was located in codon rpoB531 and katG315 . In addition, the rpoB 531 and katG mutation were more frequently observed among Beijing genotype strains than non-Beijing strains, while non-Beijing genotype showed stronger association with isolates lacking mutation in rifampicin resistance determination region ( P < 0.05). Conclusions: Our findings demonstrated that ancient Beijing MDR strains were associated with drug resistance, while modern Beijing MDR strains were more likely to be clustered. Highlights: We investigated the genetic diversity of multidrug-resistant tuberculosis strains in China. The ancient Beijing MDR strains were associated with drug resistance. The modern Beijing MDR strains were more likely to be clustered.